Analisis Faktor-Faktor Yang Mempengaruhi Keberlanjutan Badan Usaha Milik Desa (BUMDES) Terhadap Roda Perekonomian Masyarakat Desa Werot Kecamatan Likupang Selatan - Walangitan, Misael; Ponggohong, Laurens; Ponggohong, Edryl H. P.; Kamurahan, Steven Richard (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
Villages with high economic potential will be encouraged to become centers of regional economic activity. The same is true for Werot village, where with this village fund, each village can also program the establishment of a Village-Owned Enterprise (BUMDes). After being formed in 2020, the BUMDes in Werot did not function as hoped. Subsequently, when there was a change in the village head, the BUMDes was reactivated in 2023 with a focus on agriculture, acting as a distributor for agricultural products from the Werot community, such as bananas. However, several problems were found including issues with the managerial system, capital, business location, information dissemination to the community, vision and mission, long-term plans, financial reporting systems, accountability, and other issues that have yet to be revealed. Through this research, it is hoped that answers will be obtained to the key problems, enabling improvements to be made.